Ukrainian Antarctic research: current bibliography and major trends in their evolution (2016–2017) - N. G. Videnina; V. P. Rybachuk; A. P. Fedchuk; S. I. Prymachenko; N. S. Petrenko (Ukrainian Antarctic Journal, 2017)
Оbjectives of the study: to create a bibliography of scientific works of Ukrainian scientists and specialists on Antarctic research for the period 2007–2017. Bibliographic support and scientometric monitoring of the implementation of the State Special-Purpose Research Program in Antarctica for 2011–2020. Promoting the dissemination of scientific, popular scientific as well as other information about the activities of Ukraine in the Antarctic region of the planet. Methods: bibliographic search, scientometric analysis, bibliometric analysis, expert analysis, webometric analysis. Results: bibliographic descriptions and results of the bibliometric analysis of the compiled bibliography of academic papers of Ukrainian researchers on the problems of Antarctic research published in domestic and foreign publications as well as materials of international bodies of the Antarctic Treaty System from January 2016 to December 2017 are given. Conclusions: the data presented indicate a stable positive trend in the development of Ukraine’s research in the Antarcticа and the considerable contribution of domestic scientists and specialists to the world studies of the Antarctic region.